2010
DOI: 10.1080/01411920902802180
|View full text |Cite
|
Sign up to set email alerts
|

School ethnic composition and aspirations of immigrant students in Belgium

Abstract: This article examines the association between school ethnic composition and immigrant students' intentions to finish high school and to move on to higher education. We used data from 1324 immigrant and 10,546 native students gathered in the school year 2004-2005 in a sample of 85 Flemish (Belgian) secondary schools. Logistic multilevel analyses (HLM6) show that students attending schools with a majority of native students (enrolling less than 20% immigrant students) were twice as likely to plan to finish high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 43 publications
2
28
0
5
Order By: Relevance
“…Eight studies found higher levels of motivation among minority students (Choi, Bempechat, & Ginsburg, 1994;Gillen-O'Neel, Ruble, & Fuligni, 2011;Goodenow & Grady, 1993;McInerney, 2008;Sentell, 2012;Strage, 1999;Van Houtte & Stevens, 2010;Young, Johnson, Hawthorne, & Pugh, 2011), whereas six studies found higher levels of motivation among majority students (Hill et al, 2004;Hill & Wang, 2015;Sentell, 2012;Strage, 1999;Van Houtte & Stevens, 2010;Young et al, 2011). It has to be borne in mind that these studies used different instruments for the measurement of motivation, which vary from measuring intrinsic motivation (Gillen-O'Neel et al, 2011) and the intention to pursue further education (McInerney, 2008) to the motivation for academic success (intrinsic, extrinsic, and amotivation; Young et al, 2011).…”
Section: Comparison Of Motivation Of Ethnic Minority Students With Etmentioning
confidence: 99%
See 4 more Smart Citations
“…Eight studies found higher levels of motivation among minority students (Choi, Bempechat, & Ginsburg, 1994;Gillen-O'Neel, Ruble, & Fuligni, 2011;Goodenow & Grady, 1993;McInerney, 2008;Sentell, 2012;Strage, 1999;Van Houtte & Stevens, 2010;Young, Johnson, Hawthorne, & Pugh, 2011), whereas six studies found higher levels of motivation among majority students (Hill et al, 2004;Hill & Wang, 2015;Sentell, 2012;Strage, 1999;Van Houtte & Stevens, 2010;Young et al, 2011). It has to be borne in mind that these studies used different instruments for the measurement of motivation, which vary from measuring intrinsic motivation (Gillen-O'Neel et al, 2011) and the intention to pursue further education (McInerney, 2008) to the motivation for academic success (intrinsic, extrinsic, and amotivation; Young et al, 2011).…”
Section: Comparison Of Motivation Of Ethnic Minority Students With Etmentioning
confidence: 99%
“…Here 14 factors were found to be positively related with motivation: parental support (Plunkett & Bámaca-Gómez, 2003;Van Houtte & Stevens, 2010), family (guidance, material support, etc. ; Kenny et al, 2007), negative parental influence (McInerney, 2008), parental monitoring (Hill & Wang, 2015;Lowe & Dotterer, 2013;Plunkett & Bámaca-Gómez, 2003), mothers' warmth (Lowe & Dotterer, 2013), fathers' warmth (Lowe & Dotterer, 2013), parental warmth (Hill & Wang, 2015), language spoken at home (Plunkett & Bámaca-Gómez, 2003), help given by parents (Choi et al, 1994), control of parents (Choi et al, 1994), parents' help with academic tasks (Plunkett & Bámaca-Gómez, 2003), communication with caregivers (Basáñez et al, 2013), parental autonomy support (Hill & Wang, 2015), and parent-child relationship (including parental affection, parental emotional support, and parental independence encouragement; Yuan et al, 2016).…”
Section: Plans For Higher Educationmentioning
confidence: 99%
See 3 more Smart Citations